Efek Menguntungkan Dari Sa’i Dalam Ibadah Haji Terhadap Kesehatan Fisik Tubuh - Aprilla Haryanti; Ahlun Nazi Siregar; Hasiela Nurfajrina Seprizal; Mutia Arifah; Nazwa Aura rahmadani (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Hajj is one of the five pillars of Islam that must be carried out by every Muslim who meets certain requirements. The Hajj takes place in the city of Mecca, Saudi Arabia, and is considered one of the holiest and most significant pilgrimages in the Islamic religion. The formulation of the problem in this research is what are the beneficial effects of sa’I during the Hajj pilgrimage on bodily health. The aim of this research is to determine the benefits of sa’I during the Hajj pilgrimage on body health. The method in this research uses a qualitative approach with the type of library research. The results and discussion of the research are that Sa’I is not only spiritual worship that is beneficial for closeness to Allah SWT, but also physical activity that is beneficial for bodily health. The health benefits of sa’I improve fitness, maintain heart health, strengthen bones and joints, improve the immune system, reduce weight and improve mental health.